(3GdJMaI GdTGgjI aj cTa GdCSQGQ GdedcjIs - (3GdaGQSj GdTjQGRj, bWH GdOjf, eMehO Hf eSYhO Hf eUdM, (B710 (3g`s
(3ChdgG (B:s
(3QH CfYeJ aRO NjQ GdeHGOF(B... (3CeG HYO(B... (3dhdG Cf GdYGOI ShZJ ddCUGZQ GdGfHSGW Edi GdCcGHQ(B...s
(3BNQgG (B:s
(3SjeG Ef GfVGa Edi GdChd chf GdbeQ SQjYG, hGdTeS HWjFI hZjQ Pdc ef GdCSHGH hEdi GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B187s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B832s
(3cTa GdXfhf(B: (3L(B1(3, U(B367s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B407s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs